Ampulla of Vater carcinoma: advancement in the relationships between histological subtypes, molecular features, and clinical outcomes - Liang, Hao; Zhu, Yu; Wu, Ya-kun (Frontiers in Oncology, 2023)
The incidence of ampulla of Vater carcinoma, a type of periampullary cancer, has been increasing at an annual percentage rate of 0.9%. However, patients with ampulla of Vater carcinoma have quite different prognoses due to the heterogeneities of the tissue origin of this carcinoma. In addition to TNM staging, histological subtypes and molecular features of ampulla of Vater carcinoma are the key factors for predicting the clinical outcomes of patients. Fortunately, with the development of testing technology, information on the histological subtypes and molecular features of ampulla of Vater carcinoma is increasingly being analyzed in depth. Patients with the pancreaticobiliary subtype have shorter survival times. In immunohistochemical examination, high cutoff values of positive MUC1 staining can be used to accurately predict the outcome of patients. Mutant KRAS, TP53, negative SMAD4 expression and microsatellite stability are related to poor prognosis, while the clinical value of BRCA1/BRCA2 mutations is limited for prognosis. Testing the histological subtypes and molecular characteristics of ampulla of Vater carcinoma not only is the key to prognosis analysis but also provides extra information for targeted treatment to improve the clinical outcomes of patients.